Comparison of Intact Parathyroid Hormone, Alkaline Phosphatase, Phosphate Levels for Diagnosing Severe Metabolic Bone Disease in Infants with Severe Bronchopulmonary Dysplasia - Tkach, Erin K.; White, Ammie M.; Dysart, Kevin C.; Waber, Brenda; Nawab, Ursula S.; Zhang, Huayan; Jensen, Erik A. (American Journal of Perinatology, 2017)
Objective We compared the accuracy of serum intact parathyroid hormone (iPTH), alkaline phosphatase (ALP), and phosphate (phos) levels for diagnosing severe metabolic bone disease (MBD) in very low-birth-weight (VLBW) infants with severe bronchopulmonary dysplasia (BPD).Study Design Retrospective analysis of VLBW infants with severe BPD admitted between 2010 and 2012 and with ≥ 1 iPTH, ALP, and phos level collected within a similar 72-hour period. MBD severity was classified by serial radiography.Results Laboratory values were available for 65 infants, of whom 24 (36.9%) developed severe MBD. A maximum ALP > 660 IU/L was the most accurate for diagnosing severe MBD (area under the curve: 88.4%; 95% confidence interval [CI]: 77.2–94.5%). Maximum iPTH was the least accurate (optimal cut point > 130 pg/mL; area under the curve: 70.5%; 95% CI: 58.2–81.4).Conclusion Maximum ALP was more accurate than iPTH or phos for diagnosing severe MBD among preterm infants with severe BPD.
Keywords: bronchopulmonary dysplasia; metabolic bone disease; alkaline phosphatase; phosphate; intact parathyroid hormone